A SHORT STORY IN ENGLISH FOR CHILDREN WRITTEN BY HARUN YAHYA: EXPLORING THE EDUCATIONAL VALUES - bakri, Umar Bakri; Satria, Ozi; Rijnan (Journal of English Language and Literature Teaching, 2023)
The existence of literary work gives much information about the meaning of life. Reading literary work aims to comprehend messages and essential values relating to social life, religiosity, tradition, social status, personality, and society's psychology. In tune with that, this study aims to analyze educational values in a short English story for children by Harun Yahya. This study was qualitative design. The method of the study was the descriptive analysis. The technique of collecting data was library research. The technique of data analysis was content analysis. The data analysis done was organizing and familiarizing, coding and reducing, and interpreting and representing. The three data findings of the education values from a short story in English for children by Harun Yahya were Religious values (RV) in the short story message that belong to the perfection of Allah’s creation. Those reflected that awareness of walking on of life needs a way through understanding religious values, Psychology values (PV) contain the motivation to study science and Social value (SV) contains a lesson about making good relationships among fellows. Social value reflected that there is peace and safety in society's environment and awareness in holding willingness.